Menjadi Tandâ’ Binè’: Perjalanan Trisnawati Sebagai Penari Remo dan Pemain Ludruk Geddongan - Panakajaya Hidayatullah (Balai Pelestarian Nilai budaya Daerah Istimewa Yogyakarta, 2020)
This study examines the dynamics of Trisnawati’s life as a female artist in the realm of Madurese culture in Situbondo. The highlight of this research is to describe the dynamics of Trisnawati’s life journey, the problems faced by Madurese female artists, and her contribution as agents of cultural development in the regions.This study uses a qualitative approach, which elaborates the research data through in-depth interviews, literature review, and direct performance observations.The findings of this study are 1). Trisnawati’s life journey as a Madurese artist is motivated by her family, who also works as a traditional artist. Trisnawati’s artistic career began in the geddongan arena, from which she began to learn to understand the dynamics of life, absorb reality, and build her character.2). Trisnawati is known as a multitalented artist, she is a remo dancer, ludruk player, tokang kèjhung, and comedian. Her most recognizable contribution is her creation of the Remo Trisnawati dance which eventually became the attention of many dance academics and critics from various universities.3) In the realm of cultural development, Trisnawati succeeded in breaking through the dominant discourse in Madurese society which in turn opened up opportunities for women to take part in the public sphere. This also opens upnew possibilities and opportunities for the development of performing arts in Situbondo as an artistic aesthetic consequence of the involvement of female artists in the Madurese performing arts scene.